Development and validation of an HPLC-UV method for purity determination of DNA - Merve Oztug; Burhanettin Yalcinkaya (Medicine Science, 2023)
Determination of the concentration and the purity of DNAs is crucial for measuring the DNA copy number since it will influence further DNA analysis such as digital PCR (dPCR) and next-generation sequencing (NGS). Precise and scientifically validated DNA measurements empower healthcare professionals and authorities to deliver reliable outcomes. DNA agarose gel electrophoresis is commonly used to check DNA purity; however, its resolution is limited. In this study, a quantitative HPLC-UV measurement method to separate DNAs was established as an alternative to both DNA electrophoresis and spectrophotometric techniques. The method was fully validated to separate DNAs ranging between 75 and 20,000 base pairs. DNA mixtures were prepared gravimetrically. Chromatographic separations were conducted on a TSKgel DNA-NPR column with dimensions of 2.5µm, 4.6mm ID x 7.5cm, using a flow rate of 0.75 mL/min. The uncertainty of the method was assessed following the guidelines provided by EURACHEM/CITAC. The method demonstrated linearity for the 200 bp DNA fragment within the range of 0.4 ng to 800 ng DNA, with a high regression coefficient of R²=0.999. The Limit of Detection (LOD) for the 200 bp DNA fragment was determined to be 1 ng, while the Limit of Quantitation (LOQ) was found to be 3 ng. The recovery percentages for the 1%, 5%, and 10% impurities of the 150 bp DNA in 200 bp DNA fragments were measured at 101.8%, 97.4%, and 99.5%, respectively. The method established can be used in the value assignment stages of the reference materials which are required for SI traceable DNA measurements. [Med-Science 2023; 12(3.000): 876-82]